Improving sexual health for HIV patients by providing a combination of integrated public health and hospital care services; a one-group pre- and post test intervention comparison - Dukers-Muijrers Nicole HTM; Somers Carlijn; Hoebe Christian JPA; Lowe Selwyn H; Niekamp Anne-Marie EJWM; Lashof Astrid Oude; Bruggeman Cathrien AMVH; Vrijhoef Hubertus JM (BMC, 2012)
Abstract Background Hospital HIV care and public sexual health care (a Sexual Health Care Centre) services were integrated to provide sexual health counselling and sexually transmitted infections (STIs) testing and treatment (sexual health care) to larger numbers of HIV patients. Services, need and usage were assessed using a patient perspective, which is a key factor for the success of service integration. Methods The study design was a one-group pre-test and post-test comparison of 447 HIV-infected heterosexual individuals and men who have sex with men (MSM) attending a hospital-based HIV centre serving the southern region of the Netherlands. The intervention offered comprehensive sexual health care using an integrated care approach. The main outcomes were intervention uptake, patients' pre-test care needs (n=254), and quality rating. Results Pre intervention, 43% of the patients wanted to discuss sexual health (51% MSM; 30% heterosexuals). Of these patients, 12% to 35% reported regular coverage, and up to 25% never discussed sexual health topics at their HIV care visits. Of the patients, 24% used our intervention. Usage was higher among patients who previously expressed a need to discuss sexual health. Most patients who used the integrated services were new users of public health services. STIs were detected in 13% of MSM and in none of the heterosexuals. The quality of care was rated good. Conclusions The HIV patients in our study generally considered sexual health important, but the regular counselling and testing at the HIV care visit was insufficient. The integration of public health and hospital services benefited both care sectors and their patients by addressing sexual health questions, detecting STIs, and conducting partner notification. Successful sexual health care uptake requires increased awareness among patients about their care options as well as a cultural shift among care providers.